2014
DOI: 10.1111/pan.12524
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of gabapentin after scoliosis surgery in children: a randomized controlled trial

Abstract: A single preoperative dose of gabapentin did not show a significant difference in opioid consumption or pain scores in adolescents undergoing idiopathic scoliosis surgery. This study is the first pediatric randomized controlled trial to assess the effectiveness of a single dose of gabapentin on morphine consumption and analgesia following major surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 24 publications
0
43
0
2
Order By: Relevance
“…One study reported improved early pain scores and reduced opioid consumption in the first 48 hours after surgery with preoperative and postoperative gabapentin administration, 7 whereas another study found no difference in pain scores after a single preoperative dose. 15 Intravenous acetaminophen has been proposed as a useful adjuvant in pain management after major orthopedic surgery 8 and, within pediatric PSF patients, intravenous acetaminophen has been shown to improve early pain scores but has no effect on opioid consumption. 16 Ketorolac has been shown to improve analgesia and reduce opioid consumption while reducing both opioid-related gastrointestinal side effects and LOS in general pediatric orthopedic populations 17,18 and pediatric spinal fusion populations.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported improved early pain scores and reduced opioid consumption in the first 48 hours after surgery with preoperative and postoperative gabapentin administration, 7 whereas another study found no difference in pain scores after a single preoperative dose. 15 Intravenous acetaminophen has been proposed as a useful adjuvant in pain management after major orthopedic surgery 8 and, within pediatric PSF patients, intravenous acetaminophen has been shown to improve early pain scores but has no effect on opioid consumption. 16 Ketorolac has been shown to improve analgesia and reduce opioid consumption while reducing both opioid-related gastrointestinal side effects and LOS in general pediatric orthopedic populations 17,18 and pediatric spinal fusion populations.…”
Section: Discussionmentioning
confidence: 99%
“…Mayell et al 19 demonstrated that patients who received a single preoperative dose of gabapentin did not show significant improvement in opioid consumption or pain scores in this population. However, when preoperative gabapentin was used as part of a standardized RRP, including the use of intraoperative methadone and ketorolac, pain scores were improved 20…”
Section: Discussionmentioning
confidence: 89%
“…Preoperative gabapentin administration has been studied in a randomized controlled trial19 and as part of a rapid recovery pathway (RRP) for spinal fusion 20. Mayell et al 19 demonstrated that patients who received a single preoperative dose of gabapentin did not show significant improvement in opioid consumption or pain scores in this population.…”
Section: Discussionmentioning
confidence: 99%
“…no hallaron relación entre determinadas variables (edad, sexo, índice de masa corporal, posición económica familiar, grado de deformidad y duración de la cirugía) y su concepción del dolor durante el posoperatorio, lo que ayudó a sostener que el dolor es una respuesta a múltiples factores que no tienen relación entre la gravedad de la deformidad y las variables demográficas. [40][41][42][43][44] Desde la perspectiva de nuestra heterogénea población, y al revaluarla en subgrupos, podemos coincidir con dicho argumento. En otro estudio, estos mismos autores hicieron referencia a que la concepción del dolor preoperatorio es un factor predictivo importante de la duración de la estancia hospitalaria después de la cirugía, por lo cual es preciso controlarlo farmacológica y no farmacológicamente antes del procedimiento quirúrgico.…”
Section: Discussionunclassified